字典翻译 问答 高中 数学 1xn+2x(n-1)+3x(n-2)+...+(n-2)2+nx1=16[n(n+1)(n+2)]用数学归纳法证明
问题标题:
1xn+2x(n-1)+3x(n-2)+...+(n-2)2+nx1=16[n(n+1)(n+2)]用数学归纳法证明
问题描述:

1xn+2x(n-1)+3x(n-2)+...+(n-2)2+nx1=16[n(n+1)(n+2)]用数学归纳法证明

高景平回答:
  验证n=1,1=(1/6)*1*2*3   假设n时成立,验证n+1时,   1*(n+1)+2*n+...+n*2+(n+1)*1=1xn+2x(n-1)+3x(n-2)+...+(n-2)2+nx1+[1+2+3...+n+(n+1)]   =(1/6)[n(n+1)(n+2)]+(1/2)[n+2](n+1)=(1/6)(n+1)(n+2)[n+3]=(1/6)(n+1)[(n+1)+1][(n+1)+2]   所以成立,得证.
点击显示
数学推荐
热门数学推荐
  • 语文
  • 数学
  • 英语
  • 政治
  • 地理
  • 历史
  • 化学
  • 生物
  • 物理
  • 综合
  • 高考